An investigation of the control role and effectiveness of independent non-executive directors in Malaysian public listed companies - Annuar, Hairul Azlan; Ab. Rashid, Hafiz Majdi (Emerald, 2015)
Purpose – The purpose of this study is to ascertain the control role of independent non-executive directors (INEDs) in Malaysian public listed companies (PLCs), as prescribed in the Malaysian Code on Corporate Governance (MCCG).The MCCG (2000) requires substantive involvement of INEDs on the audit, nomination and remuneration board sub-committees. The study also examines the effectiveness of INEDs in discharging their monitoring roles in these sub-committees. Design/methodology/approach – A qualitative research design consisting of a series of interviews with board members of Malaysian-owned PLCs on the board of Bursa Malaysia was used. Findings – Interviews with 27 company directors reveal that, due to their independence, INEDs are crucial in safeguarding the interests of smaller investors if situations arise in which shareholders’ interests may be threatened. The interviews also disclose that the audit committee possesses the most authority among the sub-committees, as it derives its power not only from the Listing Requirements but also from statute, as well as being involved in areas of the company not traditionally associated with the committee. The study also reveals the differences in opinion between executive directors and INEDs with regard to the extent of INEDs’ effectiveness. Research limitations/implications – This research utilises interviews. Generalisation may be an issue when interviews are used as the method of inquiry. In addition, the sample is not random, as access to many directors is dependent on recommendations. In addition, the respondents have been consciously selected to cover various board positions, including independent and non-independent directors. Practical implications – The findings from this research suggest that INEDs are able to discharge their responsibilities in overseeing the conduct of executives and protecting the interests of investors. In addition, the interviews disclose that the effectiveness of INEDs depends on how non-executive directors view INEDs being on the board. Rather than focusing solely on their control role, INEDS are expected to have a more proactive and progressive role in ensuring sustainable growth and the expansion of the business entity. Originality/value – There are limited studies using qualitative research design in investigating the effectiveness of INEDs in the control role of the board in developing countries. Prior studies were predominantly based upon the experience of Western economies.